SWI/SNF protein expression status in fumarate hydratase-deficient renal cell carcinoma: immunohistochemical analysis of 32 tumors from 28 patients - Agaimy, Abbas; Amin, Mahul B; Gill, Anthony J; Popp, Bernt; Reis, André; Berney, Daniel M; Magi-Galluzzi, Cristina; Sibony, Mathilde; Smith, Steven C; Suster, Saul; Trpkov, Kiril; Hes, Ondřej; et al. (Human pathology, 2018)
Fumarate hydratase-deficient renal cell carcinoma (FH-RCC) is a rare, aggressive RCC type, originally described in the setting of hereditary leiomyomatosis and RCC syndrome, which is defined by germline FH gene inactivation. Inactivation of components of the switch/sucrose nonfermentable (SWI/SNF) chromatin remodeling complex is involved in renal medullary carcinoma (SMARCB1/INI1 loss), clear cell RCC (PBRM1 loss), and subsets of dedifferentiated RCC of clear cell, chromophobe, and papillary types (loss of different SWI/SNF components). FH-RCC and SWI/SNF-deficient RCC share anaplastic nuclear features and highly aggressive course. We analyzed 32 FH-RCCs from 28 patients using 7 commercially available SWI/SNF antibodies (SMARCB1/INI1, SMARCA2, SMARCA4, SMARCC1, SMARCC2, PBRM1, and ARID1A). Variable loss of SMARCB1, ARID1A, and SMARCC1 was observed in 1 of 31, 2 of 31, and 1 of 29 evaluable cases, respectively; 3 of these 4 SWI/SNF-deficient tumors had confirmed FH mutations. No correlation of SWI/SNF loss with solid or sarcomatoid features was observed. Two tumors with SMARCB1 and ARID1A deficiency had available SWI/SNF molecular data; both lacked SMARCB1 and ARID1A mutations. The remaining 5 SWI/SNF components were intact in all cases. Especially PBRM1 seems not to be involved in the pathogenesis or progression of FH-RCC. Our data showed that a subset of FH-RCC (12%) have a variable loss of SWI/SNF complex subunits, likely as secondary genetic events. This should not be confused with SWI/SNF-deficient RCC of other types. Evaluation of FH and SWI/SNF together with comprehensive molecular genetic profiling is needed to explore possible prognostic implications of FH/SWI-SNF double deficiency and to better understand the somatic mutation landscape in high-grade RCC.
Keywords: Male; Fumarate Hydratase; Renal cell carcinoma; lidé středního věku; Chromosomal Proteins, Non-Histone; Carcinoma, Renal Cell; Mutation; Humans; Immunohistochemistry; Fumarate hydratase; Middle Aged; karcinom z renálních buněk; DNA Helicases; senioři; Transcription Factors; ARID1A; chromozomální proteiny, nehistonové; mužské pohlaví; DNA-helikasy; Female; Kidney Neoplasms; mladiství; SWI/SNF complex; Aged; DNA vazebné proteiny; INI1; ženské pohlaví; SMARCB1; DNA-Binding Proteins; mladý dospělý; Adult; Young Adult; jaderné proteiny; transkripční faktory; Nuclear Proteins; Adolescent; fumarasa; imunohistochemie; mutace; dospělí; lidé; HLRCC; nádory ledvin